EFFICACY OF ENDOPHYTIC BACTERIA IN REDUCING PLANT PARASITIC NEMATODE Pratylenchus brachyurus - Harni, Rita; Supramana, Supramana; Supriadi, Supriadi (Indonesian Agency for Agricultural Research and Development - MOA, 2014)
Pratylenchus brachyurus is a major parasitic nematode on patchouli that reduces plant production up to 85%. The use of endophytic bacteria is promising for controlling nematode and promoting plant growth through production of phytohormones and enhancing the availability of soil nutrients. The objective of the study was to evaluate the efficacy of endophytic bacteria to control P. brachyurus on patchouli plant and its influence on plant productions (plant fresh weight and patchouli oil). The study was conducted at Cimanggu Experimental Garden and Laboratory of the Indonesian Spice and Medicinal Crops Research Institute (ISMECRI), Bogor, West Java. The experi-ment was designed in a randomized block with seven treatments and eight replications; each replication consisted of 10 plants. The treatments evaluated were five isolates of endophytic bacteria (Achromobacter xylosoxidans TT2, Alcaligenes faecalis NJ16, Pseudomonas putida EH11, Bacillus cereus MSK and Bacillus subtilis NJ57), synthetic nematicide as a reference, and non-treated plant as a control. Â Four-week old patchouli plants of cv. Sidikalang were treated by soaking the roots in suspension of endophytic bacteria (109 cfu Â ml-1) for one hour before trans-planting to the field. At one month after planting, the plants were drenched with the bacterial suspension as much as 100 ml per plant. The results showed that applications of the endophytic bacteria could suppress the nematode populations (52.8-80%) and increased plant weight (23.62-57.48%) compared to the control. The isolate of endophytic bacterium Achromobacter xylosoxidans TT2 was the best and comparable with carbofuran.